Keputusan pembelian Halal Food: Peran pengetahuan produk, labelisasi halal, dan religiusitas - Marta, Martavia; Sa’adati , Nila (Nur Science Institute, 2022)
This research examines the influence of product knowledge, halal labeling, and religiosity on purchasing decisions, with attitude as an intervening variable. This research uses a quantitative type of research. This research uses primary data by distributing questionnaires via Google Forms. The population in this research is halal food consumers in Semarang Regency. The sampling method in this study used a purposive sampling technique, and the results were obtained from 100 respondents. The data analysis used is path analysis. This research shows that product knowledge, halal labeling, and religiosity have a positive and significant effect on purchasing decisions. Product knowledge and halal labeling have a positive and significant effect on attitudes. Religiosity has a significant negative effect on attitudes. Product knowledge and halal labeling can mediate attitudes toward purchasing decisions, while religiosity cannot mediate attitudes toward purchasing decisions.